Karl Barth’s interpretative construal of the anhypostasis and enhypostasis of Christ’s human nature in relation to historical Protestant Orthodoxy - Haley, James P (Stellenbosch Theological Journal, 2017)
While it is generally agreed that the anhypostasis and enhypostasis of Christ’s human nature have a place in Karl Barth’s Christology, there is little agreement over Barth’s interpretative construal of these concepts, particularly in relation to historical Protestant Orthodoxy. In this article I argue that Karl Barth adopts both anhypostasis and enhypostasis as a dual formula to explain how the human nature of Christ exists in union with the Logos. In this way Barth moves beyond Protestant orthodox tradition wherein the patristic Fathers, Lutheran and Reformed Scholastics, and the post-Scholastic dogmatics of Heinrich Schmid (Lutheran) and Heinrich Heppe (Reformed) consistently interpret anhypostasis and enhypostasis as autonomous concepts to explain how the human nature of Christ exists in union with the Logos. What Protestant orthodoxy understood as mutually exclusive concepts to explain the human nature of Christ, Karl Barth uniquely adopts as an ontological formula to explain how the human nature of Christ exists in union with the Logos.